2017
DOI: 10.5704/moj.1707.011
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Proximal Tibia and Iliac Crest Bone Graft Donor Sites in Treatment of Orthopaedic Pathologies

Abstract: Introduction: Bone graft is harvested from bone and used to stimulate bone healing due to its properties. The aims of the study were to compare the quantity of graft harvested from proximal tibia and iliac crest, and the complications at these donor sites.Materials and Methods: This was a prospective study carried out on all consecutive patients who had orthopaedic procedures that required bone grafting at the study centre, from April, 2015 to March, 2016.Results: During the study period, 86 patients were recr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…In our study, we harvested the bone graft as much as possible during surgery. Even the graft volume from proximal tibia was larger than the iliac crest, the proximal tibia donor site gave less complication than the iliac crest, according to the report of Salawu et al [ 25 ], and the present study’s result showed there was less pain in the proximal tibia harvest site. The lack of comparison of quantity of harvest graft is one our limitations, and bone harvest at two sites of the same person simultaneously for the comparison of volume was also not practicable in our retrospective study.…”
Section: Discussionsupporting
confidence: 62%
“…In our study, we harvested the bone graft as much as possible during surgery. Even the graft volume from proximal tibia was larger than the iliac crest, the proximal tibia donor site gave less complication than the iliac crest, according to the report of Salawu et al [ 25 ], and the present study’s result showed there was less pain in the proximal tibia harvest site. The lack of comparison of quantity of harvest graft is one our limitations, and bone harvest at two sites of the same person simultaneously for the comparison of volume was also not practicable in our retrospective study.…”
Section: Discussionsupporting
confidence: 62%
“…The authors chose the latter since evidence suggests that there is no significant difference in the volume of cancellous bone available for harvest between the PT and iliac crest [11] . Furthermore, utilising the PT as a harvest site causes fewer complications such as pain, primary haemorrhage, and surgical site infection [12] , [13] .…”
Section: Discussionmentioning
confidence: 99%
“…Carlock et al reported a high union rate after ICBG, with 232 unions in 242 treated patients [ 35 ]. Furthermore, On Salawu et al reported a higher union rate following ICBG, with 81 unions in 86 patients [ 36 ]. In this regard, the data in the literature are controversial, because the RIA group is characterized by a higher union rate [ 17 , 25 ].…”
Section: Discussionmentioning
confidence: 99%